Pengembangan Media Edukasi Buku Komik tentang Covid-19 untuk Anak Sekolah Dasar - Oktaviani, Eva; Jawiah, Jawiah; Rehana, Rehana; Setiyono, Imawan Eko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
We aimed to summarize the development process of developing the Covid-19 comic book as a prevention medium through a literary work. Research and Development was used as the method in this research with 4 D approach (Define, Design, Develop, Disseminate). The research results show that the average comic validation test score is 4.61 for material experts, 4.24 for media experts, and 4.58 for practitioners. Comic books about education during the Covid-19 pandemic are very suitable to be used as health promotion media about Covid-19. The results of limited trials (n=100) described the stories in comics as very interesting (85%), easy to understand (85%), and useful (100%). In conclusion, the Covid-19 comic book has been declared very suitable as a health promotion medium for children during the pandemic. Attractive Media literacy is currently being encouraged to support children's learning in the concept of understanding Covid-19 and increase children's awareness of implementing health protocols during the pandemic. Keywords: Comic Book, Covid-19, Pandemic